Assimilation of SEVIRI Water Vapour Radiances in HARMONIE-AROME at Large Satellite Zenith Angles - David Schönach; Reima Eresmaa; Heikki Järvinen (Tellus: Series A, Dynamic Meteorology and Oceanography)
This study suggests potential benefits in forecast performance by assimilating clear-sky satellite radiances from geostationary based SEVIRI instrument into the limited area model of HARMONIE-AROME in the far North of Europe. The current geographical limitations of assimilating geostationary have been breached and a series of data assimilation experiments were conducted over a winter period to assess the impact of including SEVIRI water vapor channels at large satellite zenith angles. The results suggest improved background departures and improved analyses for humidity and temperature fields and subsequent enhancements in forecast skill in surface meteorological parameters like pressure, temperature, humidity and clouds. The findings highlight opportunities for using geostationary satellite data beyond current limitations and identify areas for further improvements.